2022
DOI: 10.3390/su14137656
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Driving Mechanism of Tourism Flow Networks in the Yangtze River Delta Urban Agglomeration Based on Social Network Analysis and Geographic Information System: A Double-Network Perspective

Abstract: This study’s purpose was to analyze the network structural characteristics, nodal roles, spatial structure, and evolution laws from the dual network perspective, and apply the Quadratic Assignment Procedure (QAP) to conduct correlation analysis and regression analysis on the influencing factors of tourism flow networks in the Yangtze River Delta urban agglomerations. Using a mixed-method of social network and spatial analysis, Ucinet and ArcGIS software were used to comprehensively analyze the nodes in the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…It can also be applied to regression analysis of matrices and examine interaction effects between multiple networks [45]. The method has been shown to be robust and reliable by several scholars [46][47], avoiding issues of multiple collinearities of independent variables in causality analysis.…”
Section: Quadratic Assignment Proceduresmentioning
confidence: 99%
“…It can also be applied to regression analysis of matrices and examine interaction effects between multiple networks [45]. The method has been shown to be robust and reliable by several scholars [46][47], avoiding issues of multiple collinearities of independent variables in causality analysis.…”
Section: Quadratic Assignment Proceduresmentioning
confidence: 99%
“…It usually refers to the system that combines spatial geographic information with tourism information under the network environment and virtually realizes the tourism information service system with a sense of authenticity in the computer network. It is a digital realization of the whole process of tourism (Wang et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yin et al identified a set of factors that affect tourism cooperation in China-ASEAN including differences in political system, governance, and income [28]. In addition to the abovementioned factors influencing cooperation between tourism destinations from the perspective of supply (including governments and enterprises), some scholars have also analyzed factors influencing cooperation between tourism destinations from the perspective of demand [29][30][31][32]. The multidestination tourism behavior of tourists is regarded as the driving factor of cooperation among tourism destinations [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the abovementioned factors influencing cooperation between tourism destinations from the perspective of supply (including governments and enterprises), some scholars have also analyzed factors influencing cooperation between tourism destinations from the perspective of demand [29][30][31][32]. The multidestination tourism behavior of tourists is regarded as the driving factor of cooperation among tourism destinations [29][30][31][32]. The spatial behavior and movement of tourists' free choice objectively connect different tourist destinations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation